Information services for smart grids - King, R.L. (2008 IEEE Power and Energy Society General Meeting - Conversion and Delivery of Electrical Energy in the 21st Century, 2008)
Interconnected and integrated electrical power systems, by their very dynamic nature are complex. These multifaceted systems are subject to a host of challenges - aging infrastructure, generation availability near load centers, transmission expansion to meet growing demands, distributed resources, dynamic reactive compensation, congestion management, grid ownership vs. system operation, reliability coordination, supply and cost of natural resources for generation, etc. Other types of challenges facing the industry today include balancing between resource adequacy, reliability, economics, environmental constraints, and other public purpose objectives to optimize transmission and distribution resources to meet the needs of the end users. The goal is to provide a vision for a comprehensive and systematic approach to meeting the grid management challenges through new information services. These services will have as the heart of their data streams a sensor web enablement that will make the grid a part of the semantic Web.